Religion in the anthropocene - Deane-Drummond, Celia; Bergmann, Sigurd, 1956-; Vogt, Markus, 1962-; Bedford-Strohm, Heinrich (The Lutterworth Press, 2018)
A multidisciplinary collection of essays exploring the many social, ethical and theological aspects of the Anthropocene, the geological Age of Humans.